(untitled) (The Shivapuri Journal, 2026)
Eco-tourism plays crucial role connecting biodiversity conservation with rural livelihoods around Nepal’s protected areas, however, climate change is emerging as a threat to its ecological and socio-economic foundations. This study is concerned with the impacts of climate change on eco-tourism in Chitwan National Park (CNP) and its buffer zone, with particular emphasis on community adaptation and institutional response within eco-tourism systems. The study applies mixed-methods following explanatory sequential design combining a household (n = 385) survey with key informant interviews and focus group discussions. A majority of households observe temperature fluctuations and rainfall variability, protracted dry seasons, floods, and riverbank erosion impacting their wildlife habitats, modes of tourism and source of livelihood by slowing down tourist inflow and income stability. Although households are taking strategies like livelihood diversification and community conservation activities, institutional support is inconsistent. Applying Political Ecology, Triple-Bottom-Line Sustainability and Adaptive Capacity, the analysis underpins an analysis that detects governance deficits and recently emerging conflict sensitivities concerning participation and benefit-sharing, emphasizing the role of cogovernance with climate responsiveness to enhance eco-tourism resilience in Nepal’s lowland protected areas.